Eksplorasi laminasi kayu dalam desain nakas dengan pendekatan estetika Ukir Jepara - Bagas Surya Pratama; Jati Widagdo; Achmad Zainudin (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
Furniture is one of the most important and prioritized aspects of life. Furniture is one of the main needs for decoration and interior elements, which refers to various furniture elements used to complement and decorate spaces in a building. This work highlights innovation in furniture design through the creation of a culture-based laminated bedside table, with the aim of preserving the tradition of Jepara carvings. As a rich cultural heritage, Jepara carvings represent a local identity that has high aesthetic and historical value. However, modernization and changes in lifestyle have led to a decline in interest in this traditional product. This study aims to integrate modern lamination techniques with traditional carving motifs, producing a product that is relevant to the needs of the contemporary market while maintaining the sustainability of cultural traditions. The design and production process involves exploring Jepara's typical carving patterns applied to laminated materials, producing a functional, aesthetic, and innovative bedside table. The results of this creation are expected to not only strengthen the appeal of Jepara carvings in the local and global markets, but also increase public awareness of the importance of preserving traditional cultural arts. This study makes a significant contribution to the development of culture-based product design as part of efforts to preserve traditions in the modern era.